A Case Study on Telmisartan Induced Acute Kidney Injury - Surendran, Kavya; Joseph, Beenu Maria; Vilapurathu, Jobin Kunjumon (Journal of Pharmacy Practice and Community Medicine)
Telmisartan is a widely used antihypertensive drug that effectively lowers blood pressure. In this report, we present the case of a patient who developed acute kidney injury after taking an ARB inhibitor, Telmisartan. A 40-year old, male patient who is known case of Congestive heart failure and dilated cardiomyopathy got admitted to the emergency department with breathlessness and cough. He was diabetic for the past four years and was on Insulin. He was also hypertensive for the past 11 years and was on Telmisartan. All his blood parameters except renal function tests (blood urea, creatinine, potassium, sodium) were normal during hospitalization. Cardiac markers (d-dimer and troponins) were within normal limits, but the ECG report revealed sinus tachycardia and left ventricular hypertrophy. Echocardiography report showed Global left ventricular hypokinesia, dysfunction of the left ventricle, moderate pulmonary arterial hypertension, moderate mitral regurgitation, dilated left arterial and ventricular enlargement. Chest X-ray showed cardiomegaly. High Blood pressure was controlled with ARB Inhibitor- Telmisartan. Uncontrolled hypertension caused a change in dose during admission, which could explain the sudden kidney injury. The drug was discontinued abruptly and switched over to an alpha-blocker- Prazosin. A decrease in serum creatinine levels indicated improvement in the patient’s condition in the following days. Hence, we bring your attention to the possibility that all aged patients with or without a compromised cardiac function must undergo careful monitoring to prevent such adverse events due to the drug (Telmisartan). Also, it is prudent to consider the possibility of cardio-renal syndrome for fewer unwanted events.
Keywords: Angiotensin receptor blockers; Telmisartan; Acute kidney injury; Angiotensin receptor blockers; Kidney function